The impact of dark-blood versus conventional bright-blood late gadolinium enhancement on the myocardial ischemic burden. Issue 144 (November 2021) - Franks, Russell; Holtackers, Robert J.; Alskaf, Ebraham; Nazir, Muhummad Sohaib; Clapp, Brian; Wildberger, Joachim E.; Perera, Divaka; Plein, Sven; Chiribiri, Amedeo
Abstract: Purpose: In perfusion cardiovascular magnetic resonance (CMR), ischemic burden predicts adverse prognosis and is often used to guide revascularization. Ischemic scar tissue can cause stress perfusion defects that do not represent myocardial ischemia. Dark-blood late gadolinium enhancement (LGE) methods detect more scar than conventional bright-blood LGE, however, the impact on the myocardial ischemic burden estimation is unknown and evaluated in this study. Methods: Forty patients with CMR stress perfusion defects and ischemic scar on both dark-blood and bright-blood LGE were included. For dark-blood LGE, phase sensitive inversion recovery imaging with left ventricular blood pool nulling was used. Ischemic scar burden was quantified for both methods using >5 standard deviations above remote myocardium. Perfusion defects were manually contoured, and the myocardial ischemic burden was calculated by subtracting the ischemic scar burden from the perfusion defect burden. Results: Ischemic scar burden by dark-blood LGE was higher than bright-blood LGE (13.3 ± 7.4% vs. 10.3 ± 7.1%, p < 0.001). Dark-blood LGE derived myocardial ischemic burden was lower compared with bright-blood LGE (15.6% (IQR: 10.3 to 22.0) vs. 19.3 (10.9 to 25.5), median difference −2.0%, p < 0.001) with a mean bias of −2.8% (95% confidence intervals: −4.0 to −1.6%) and a large effect size (r = 0.62). Conclusion: Stress perfusion defects are associated with higher ischemic scar burden using dark-blood LGE compared with bright-blood LGE, which leads to a lower estimation of the myocardial ischemic burden. The prognostic value of using a dark-blood LGE derived ischemic burden to guide revascularization is unknown and warrants further investigation.